Autism spectrum disorder and a possible role of anti-inflammatory treatments: experience in the pediatric allergy/immunology clinic - Jyonouchi, Harumi (Frontiers in Psychiatry, 2024)
Autism spectrum disorder (ASD 1 ) is a behaviorally defined syndrome encompassing a markedly heterogeneous patient population. Many ASD subjects fail to respond to the 1 st line behavioral and pharmacological interventions, leaving parents to seek out other treatment options. Evidence supports that neuroinflammation plays a role in ASD pathogenesis. However, the underlying mechanisms likely vary for each ASD patient, influenced by genetic, epigenetic, and environmental factors. Although antiinflammatory treatment measures, mainly based on metabolic changes and oxidative stress, have provided promising results in some ASD subjects, the use of such measures requires the careful selection of ASD subjects based on clinical and laboratory findings. Recent progress in neuroscience and molecular immunology has made it possible to allow re-purposing of currently available anti-inflammatory medications, used for autoimmune and other chronic inflammatory conditions, as treatment options for ASD subjects. On the other hand, emerging anti-inflammatory medications, including biologic and gatekeeper blockers, exert powerful anti-inflammatory effects on specific mediators or signaling pathways. It will require both a keen understanding of the mechanisms of action of such agents and the careful selection of ASD patients suitable for each treatment. This review will attempt to summarize the use of anti-inflammatory agents already used in targeting ASD patients, and then emerging anti-inflammatory measures applicable for ASD subjects based on scientific rationale and clinical trial data, if available. In our experience, some ASD patients were treated under diagnoses of autoimmune/autoinflammatory conditions and/or post-infectious neuroinflammation. However, there are little clinical trial data specifically for ASD subjects. Therefore, these emerging immunomodulating agents for potential use for ASD subjects will be discussed based on preclinical data, case reports, or data generated in patients with other medical conditions. This review will hopefully highlight the expanding scope of immunomodulating agents for treating neuroinflammation in ASD subjects..